Workplace violence types in family health, offenders, reactions, and problems experienced - Sturbelle,Isabel Cristina Saboia (2020)
ABSTRACT Objective: to identify the types of violence that affect the health team in Family Health Units, their offenders, reactions and problems experienced by workers. Method: a cross-sectional, concurrent mixed-type research. The Survey Questionnaire Workplace Violence in the Health Sector was applied to 106 workers from Family Health Units. Of these, 18 answered the semi-structured interview. Results: verbal aggression (65.1%), bullying (14.2%), racial discrimination (10.4%), physical assault (8.5%) and sexual harassment (4.7%) were prevalent. Patients were the main perpetrators of verbal aggression (79.4%) and bullying (46.7%). Workers responded by telling co-workers and reporting to the boss. Victims remained over-alert, vigilant and tense, relating exposure to violence to absenteeism and the desire to leave the profession. Conclusion: verbal aggression is the most common violence with negative impact on workers’ health and work performed.